2010
DOI: 10.1002/cncr.25439
|View full text |Cite
|
Sign up to set email alerts
|

The molecular pathogenesis of hereditary ovarian carcinoma

Abstract: BACKGROUND: BRCA1 or BRCA2 (BRCA1/2)-mutated ovarian carcinomas may originate in the fallopian tube. The authors of this report investigated alterations in BRCA1/2 tubal epithelium to define the molecular pathogenesis of these carcinomas. METHODS: Tubal epithelium was evaluated from 31 BRCA1/2 mutation carriers with gynecologic carcinomas (BRCA CA), 89 mutation carriers who underwent risk-reducing salpingo-oophorectomy (RRSO), and 87 controls. Ki-67 expression and p53 foci (!10 of 12 consecutive staining cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 92 publications
3
46
1
Order By: Relevance
“…All of the women in our control group underwent RRSO because of a family history of ovarian cancer or personal history of breast cancer; all had normal pre-operative CA 125 and ultrasound. Also, unlike the control group in other studies, our control group of patients had genetic testing and no BRCA mutations were detected [9,13,19,21].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…All of the women in our control group underwent RRSO because of a family history of ovarian cancer or personal history of breast cancer; all had normal pre-operative CA 125 and ultrasound. Also, unlike the control group in other studies, our control group of patients had genetic testing and no BRCA mutations were detected [9,13,19,21].…”
Section: Discussionmentioning
confidence: 97%
“…In a smaller cohort of 75 BRCA mutation carriers, Saleemuddin et al correlated p53 signatures in fallopian tubes removed at RRSO with less robust risk factors for ovarian cancer and found a relationship between older age at first birth and lower parity and p53 signatures [27]. The relatively high frequency of p53 overexpression in tubal epithelium among BRCA mutation carriers and controls suggests that alterations in genes other than or in addition to p53 are needed to promote neoplastic transformation in the fallopian tube [13,18,19,26]. Norquist et al showed that foci of p53 overexpression in BRCA1 mutation carriers had decreased p27 expression compared to BRCA2 and control patients and suggested a possible role for cyclin-dependent kinase inhibitor 1B (CDKN1B) (which encodes p27) in BRCA1 tubal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hormone producing) cells (Chodankar, et al 2005; Hong, et al 2010; Yen, et al 2012) and in humans with either a BRCA1 or BRCA2 mutation (Widschwendter, et al 2013) demonstrated that BRCA mutations confers higher serum (circulating) levels of both estrogen and progesterone. Moreover, serous tubal intra-epithelial carcinoma in the distal end of the fallopian tube was discovered in 10-15% of BRCA carriers who had prophylactic salpingo-oophorectomy (Folkins, et al 2008; Norquist, et al 2010). Ultimately, little mechanistic information exists related to the impact that hormones have on the prevention and/or pathogenesis of ovarian cancer.…”
Section: Ovarymentioning
confidence: 99%